Adsorption of divalent cadmium by calcified iron-embedded carbon beads. Issue 11 (10th February 2020) - Cheng, Yalin; Wang, Kaiqian; Tu, Biyang; Xue, Shan; Deng, Jiahui; Tao, Haisheng
Abstract : The material structure could prevent Fe nanoparticle agglomeration during synthesis and maintain Fe stability during adsorption. Fe/SA-C had a superior adsorption property and easy recoverability. Abstract : A novel iron-embedded carbon bead was prepared by the calcination of a calcium alginate gel bead mixed with iron nanoparticles coated by polydopamine. The prepared iron-embedded carbon bead was characterized by infrared spectrum analysis, X-ray diffraction, Raman spectroscopy, vibrating sample magnetometry, X-ray photoelectron spectroscopy, scanning electron microscopy and transmission electron microscopy. It was discovered that the novel structure efficaciously prevented the agglomeration of iron nanoparticles. Additionally, the effects of dose, pH, exposure time, temperature and initial concentration on the adsorption of Cd(ii ) were studied, and the reusability of the material was analyzed. Fe/SA-C showed high Cd(ii ) removal capability (220.3, 225.7, 240.8 mg g −1 at 288, 298, 308 K), easy recoverability and high stability. In addition, some slightly different interpretations of the adsorption mechanism are given. This study clearly revealed that Fe/SA-C has potential application in the removal of Cd(ii ).